ESG MANAGEMENT AND FOREIGN EXPERIENCE IN IT (Global Conference on Multidisciplinary Research and Innovation, 2026)
This thesis analyzes the theoretical foundations of the concept of sustainable development, the stages of its formation, and its significance in modern economic, environmental, and social processes. It also analyzes institutional, strategic, and integrated management approaches to sustainable development used in international practice, and considers the possibilities of their application to the activities of economic entities.
Keywords: Sustainable development